2019
DOI: 10.1021/acsami.9b10531
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Functionalization of Graphene Oxide with a Presynthesized Metal–Organic Framework Enables a Highly Stable Electrochemical Sensing

Abstract: This paper reports the covalent functionalization of graphene oxide (GO) by a presynthesized metal−organic framework NH 2 -MIL-101(Fe) via ultrasonication of the two components. The formation of Fe−O covalent bonding in the NH 2 -MIL-101(Fe)-GO nanohybrid is clearly evidenced, and the covalent bonding still remains after electrochemical reduction. The morphology and structure of the nanohybrid are characterized via scanning electron microscopy, transmission electron microscopy, UV−vis spectroscopy, Fourier tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…[ 44 ] However, the peak of CO bonds in YbHHTP (288.46 eV) shifts to a higher binding energy (288.91 eV) after its integration with GO, suggesting the possible electronic interaction between GO and MOF. [ 35 ] An identical binding energy of 185.52 eV was observed in Yb 4d spectra of YbHHTP and GO/YbHHTP (Figure 2d), [ 45 ] suggesting that the Yb 3+ oxidation state in MOF is not disturbed by the presence of GO. In the spectra of O 1s, YbHHTP and GO/YbHHTP exhibit the identical binding energies corresponding to OH bonds of adsorbed water (533.61 eV), CO (533.05 eV) and CO (531.73 eV) bonds in the coordinated catecholate, and YbO bonds (530.69 eV) (Figure S7, Supporting Information), respectively.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…[ 44 ] However, the peak of CO bonds in YbHHTP (288.46 eV) shifts to a higher binding energy (288.91 eV) after its integration with GO, suggesting the possible electronic interaction between GO and MOF. [ 35 ] An identical binding energy of 185.52 eV was observed in Yb 4d spectra of YbHHTP and GO/YbHHTP (Figure 2d), [ 45 ] suggesting that the Yb 3+ oxidation state in MOF is not disturbed by the presence of GO. In the spectra of O 1s, YbHHTP and GO/YbHHTP exhibit the identical binding energies corresponding to OH bonds of adsorbed water (533.61 eV), CO (533.05 eV) and CO (531.73 eV) bonds in the coordinated catecholate, and YbO bonds (530.69 eV) (Figure S7, Supporting Information), respectively.…”
Section: Resultsmentioning
confidence: 77%
“…[ 30–34 ] In particular, Zhu and co‐workers have reported a physical mixing process to prepare highly stable NH 2 –MIL‐101(Fe)–GO (MIL = Materials of Institute Lavoisier) composites for the detection of purines and their metabolites. [ 35 ] Wang and co‐workers have demonstrated the low concentration detection of DA and UA with the aid of the in situ grown GO–ZIF‐67 (ZIF = zeolitic imidazolate framework) composites. [ 36 ] However, the rational integration of conductive MOFs and GO for electrochemical sensing has not been yet reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 133 ] Based on current studies, composites of graphene/MOF‐based materials could integrate their superiorities and eliminate individual defections, leading the composites with enhanced stability and improved electroconductivity. [ 134–136 ] Alkordi and co‐workers produced a composite of HKUST‐1/graphene by one‐pot synthesis technology. [ 137 ] They found that the moldable composite materials allowed for an adjustable graphene content, in which the high electrical conductivity (from 7.6 × 10 –3 to 640 S cm −1 ) was positively correlated to the graphene loadings.…”
Section: Enhancing the Conductivity Of Mof‐derived Nanostructuresmentioning
confidence: 99%
“…Covalent functionalization involves strong molecular bonding between GDs and azobenzenes, which inevitably results in partial damage of π-conjugated structures. However, strong chemical bonds at an interface facilitate precise control and modulation of electronic properties of the composite material, contributing to efficient charge or energy transfer and quantum effects [101,102]. Many GD-AZO composites synthesized by covalent functionalization develop non-covalent interactions after composite formation, significantly influencing the properties of the composites.…”
Section: Covalent Linkagesmentioning
confidence: 99%